Gasification reactor engineering approach to understanding the formation of biochar properties - Rollinson, Andrew (Royal Society, 2016)
Operational reactor temperatures (spanning the reduction zone), pressure, and product gas composition measurements from a downdraft gasifier were compared against subsequent biochar elemental composition, surface morphology and PAH content. Pine feedstock moisture (FM), with values of 7% and 17% was the experimental variable. Moderately high steady-state temperatures were observed inside the reactor, with a ca. 50°C difference in how the gasifier operated between the two feedstock types. Both chars exhibited surface properties comparable to activated carbon, but the relatively small differences in temperature caused significant variations in biochar surface area and morphology: micropore area 584 m2.g-1 (FM7%) against 360 m2.g-1 (FM17%), and micropore volume 0.287 cm3.g-1 (FM7%) against 0.172 cm3.g-1 (FM17%). Differences in char extractable PAH content were also observed, with higher concentrations (187 μg.g-1 15 ± 18) when the gasifier was operated with FM7%, compared to 89 ± 19 μg.g-1 Σ16EPA PAH with FM17%. It is recommended that greater detail on operational conditions during biochar production should be incorporated as standard to future biochar characterisation research as a consequence of these results.